2018
DOI: 10.1093/hmg/ddy212
|View full text |Cite
|
Sign up to set email alerts
|

AAV9 intracerebroventricular gene therapy improves lifespan, locomotor function and pathology in a mouse model of Niemann–Pick type C1 disease

Abstract: Niemann–Pick type C disease (NP-C) is a fatal neurodegenerative lysosomal storage disorder. It is caused in 95% of cases by a mutation in the NPC1 gene that encodes NPC1, an integral transmembrane protein localized to the limiting membrane of the lysosome. There is no cure for NP-C but there is a disease-modifying drug (miglustat) that slows disease progression but with associated side effects. Here, we demonstrate in a well-characterized mouse model of NP-C that a single administration of AAV-mediated gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…The standard approach to gene therapy of the brain is the use of adeno-associated virus (AAV), and certain AAV serotypes, such as AAV9, cross the BBB following IV administration 8 . The use of ssAAV, which has twice the cloning capacity of scAAV 9 , and the development of mini-promoters, allows for the insertion of a large therapeutic gene such as the 3.9 kb NPC1 open reading frame into the AAV genome 22,23,24 . The NPC1 gene with a 227 nucleotide elongation factor-1α (EF1α) promoter was delivered to NPC1 −/− mouse brain with AAV9 following IV administration of high injection doses (ID), 1-2 × 10 14 vg/kg of the virus 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The standard approach to gene therapy of the brain is the use of adeno-associated virus (AAV), and certain AAV serotypes, such as AAV9, cross the BBB following IV administration 8 . The use of ssAAV, which has twice the cloning capacity of scAAV 9 , and the development of mini-promoters, allows for the insertion of a large therapeutic gene such as the 3.9 kb NPC1 open reading frame into the AAV genome 22,23,24 . The NPC1 gene with a 227 nucleotide elongation factor-1α (EF1α) promoter was delivered to NPC1 −/− mouse brain with AAV9 following IV administration of high injection doses (ID), 1-2 × 10 14 vg/kg of the virus 22 .…”
Section: Discussionmentioning
confidence: 99%
“…--SRT (Platt et al, 1997) (Sango et al, 1995) + + AAV (Sargeant et al, 2011;Cachon-Gonzalez et al, 2014), BMT (Norflus et al, 1998;Wada et al, 2000), CM (Pelled et al, 2003), Diet (Denny et al, 2010), HSP (Kirkegaard et al, 2016), MIP-1 (Wu and Proia, 2004), SRT (Jeyakumar et al, 1999) HexB ( Npc1 (−/−) (Morris et al, 1977) + -AAV (Chandler et al, 2017b;Xie et al, 2017;Hughes et al, 2018), AI (Alvarez et al, 2008), AO (Fu et al, 2013), CM (Erickson et al, 2000;Repa et al, 2007;Abi-Mosleh et al, 2009;Liu et al, 2010;Taylor et al, 2012;Hovakimyan et al, 2013;Nusca et al, 2014;Tanaka et al, 2014;Soga et al, 2015;Demais et al, 2016), Diet (Jelinek et al, 2015;Soga et al, 2015), HSP (Chung et al, 2016;Kirkegaard et al, 2016), NS (Griffin et al, 2004;Liao et al, 2009), Transplant (Veyron et al, 1996) Npc1 (Otterbach and Stoffel, 1995) + +…”
Section: Metachromatic Leukodystrophymentioning
confidence: 99%
“…The I1061T mutant, which harbors the most common human NPC1 mutation, was generated to specifically study the effects of proteostatic modulation on disease progression. Various preclinical trials including GT, ERT, and transplant in these models have shown different but promising levels of success in prolonging mutant lifespan, reducing Purkinje cell atrophy and the storage phenotype (Veyron et al, 1996;Soga et al, 2015;Chandler et al, 2017b;Xie et al, 2017;Hughes et al, 2018).…”
Section: Metachromatic Leukodystrophy (Mld Omim #250100)mentioning
confidence: 99%
“…Therefore, the use of in vivo disease models allows investigators to observe and analyze symptomatic manifestation of NDDs alongside with the therapeutic outcomes of their experimental treatment. This also aids in getting a comprehensive insight into the complex interconnection between etiological and symptomatic changes during the progression of NDDs, such as neuronal ceroid lipofuscinosis (NCL or Batten disease) [35], spinal muscular atrophy [101], or Niemann-Pick disease [102], whose development is typically associated with genetic perturbations in multiple genes. Therefore, in contrast to in vitro models, a mouse model of NDD would allow recapitulating onset and progression of the counterpart human disease of a given degree of severity.…”
Section: In Vitro Vs In Vivo Modelsmentioning
confidence: 99%